Pembuatan Puzzle Adventure Game Menggunakan Unity - Stevie Yohanes; Gregorius Satia Budhi; Liliana Liliana (Jurnal Infra, 2016)
Puzzle Adventure Game is a game that has the form of games exploring a region or a place in which to complete a story on where the player should be able to complete a variety of challenges that are often shaped puzzles and such.This game is made with a reason to teach a variety of moral values are positive through the game, because a lot of games today do not give you the material into his game. This game also comes with a variety of functions such as save game, load game, resolution settings, sound settings, as well as game-style point-and-click. It is intended to be able to make the players comfortable playing. Once created, these games can be played well without any interruption or bugs, and also can be played in almost all computer that has 2GB RAM and above. Thanks to game development using Unity and various assets in it, making the game becomes easier so that the games can be designed in such a way in a very limited time. The time used to make the game is less than 4 month, though the content of the game is not yet perfect but the game successfully run with perfection without bug.